The Impact of Graphic Design on Product Branding from the Perspective of Graphic Design Students at Saudi Universities as A Model - Abdelmaqsoud, Mohammed Gamal Mohammed; Mohamed Assal, Mohamed Elsayed Ali; Abdealsalam Hosen, Reham Mohyealdeen Mohamed (Journal of Posthumanism, 2025)
This study explores the impact of graphic design on product branding from the perspective of graphic design students at Saudi public universities. The primary aim of the research was to assess students’ understanding of branding and their perception of graphic design’s role in shaping brand identity and influencing consumer behavior. The study targeted 88 male and female graphic design students across six major Saudi universities, including King Saud University, Imam Mohammad Ibn Saud Islamic University, and others from different regions. A structured questionnaire was administered to collect data, and descriptive statistical analysis was used to evaluate the results. The findings revealed that a significant majority of students (85.2%) agreed that graphic design plays a crucial role in branding, with logos (79.5%) and color schemes (72.7%) identified as the most influential design elements. While the students expressed moderate to high self-assessed knowledge of branding, 19.3% of respondents were dissatisfied with the branding-related content in their curricula, suggesting gaps in practical training and real-world application. The study concludes that while graphic design students in Saudi Arabia recognize the strategic importance of design in branding, there is a need for curriculum improvements to better prepare students for real-world branding challenges. Based on these findings, the study recommends enhancing branding education in design curricula, integrating practical projects and industry collaborations, offering workshops with industry professionals, and updating teaching tools to reflect current industry standards.